Feminist and Women Empowerment in Nyad (2023): A Feminist Analysis of Diana Nyad’s Struggle - Ajriya Azmi, Hasna; Widiyanti, Ana (Metaphor, 2025)
This study discusses feminist values and the representation of women’s empowerment in the film Nyad (2023). The film is based on the true story of Diana Nyad, a woman who attempts to fulfill her lifelong dream of swimming from Cuba to Florida at the age of 60. This research aims to find out how feminist values are represented in the film and how women’s empowerment is shown through the main character. The theory used in this research is Simone de Beauvoir’s feminist theory, especially the idea that women are often seen as “the Other.” This study applies a descriptive qualitative method, with the main data taken from dialogues in the film. The data were collected by watching, identifying, classifying, and analyzing scenes related to feminist values and acts of empowerment. The results show six feminist values in the film, namely equality, resistance, agency, solidarity, empowerment, and self-determination. The film also shows how Diana fights against age limitations, public doubt, and social pressure. The film delivers a message that women deserve to be heard, respected, and given equal opportunities in life.